Step
*
2
1
2
of Lemma
finite-Ramsey1
1. c : ℕ
2. ∀c:ℕc. ∀s:ℕc ⟶ ℕ.
     ∃N:ℕ+
      ∀g:ℕN ⟶ ℕN ⟶ ℕc. ∃i:ℕc. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
3. s : ℕc ⟶ ℕ
4. ¬(c = 0 ∈ ℤ)
5. c = 1 ∈ ℤ
6. ¬0 < s 0
⊢ ∃N:ℕ+
   ∀g:ℕN ⟶ ℕN ⟶ ℕ1. ∃i:ℕ1. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
BY
{ TACTIC:((D 0 With ⌜1⌝  THEN Auto) THEN (D 0 With ⌜0⌝  THENA Auto)) }
1
1. c : ℕ
2. ∀c:ℕc. ∀s:ℕc ⟶ ℕ.
     ∃N:ℕ+
      ∀g:ℕN ⟶ ℕN ⟶ ℕc. ∃i:ℕc. ∃f:ℕs i ⟶ ℕN. (Inj(ℕs i;ℕN;f) ∧ (∀a,b:ℕs i.  (f a < f b 
⇒ ((g (f a) (f b)) = i ∈ ℤ))))
3. s : ℕc ⟶ ℕ
4. ¬(c = 0 ∈ ℤ)
5. c = 1 ∈ ℤ
6. ¬0 < s 0
7. g : ℕ1 ⟶ ℕ1 ⟶ ℕ1
⊢ ∃f:ℕs 0 ⟶ ℕ1. (Inj(ℕs 0;ℕ1;f) ∧ (∀a,b:ℕs 0.  (f a < f b 
⇒ ((g (f a) (f b)) = 0 ∈ ℤ))))
Latex:
Latex:
1.  c  :  \mBbbN{}
2.  \mforall{}c:\mBbbN{}c.  \mforall{}s:\mBbbN{}c  {}\mrightarrow{}  \mBbbN{}.
          \mexists{}N:\mBbbN{}\msupplus{}
            \mforall{}g:\mBbbN{}N  {}\mrightarrow{}  \mBbbN{}N  {}\mrightarrow{}  \mBbbN{}c
                \mexists{}i:\mBbbN{}c.  \mexists{}f:\mBbbN{}s  i  {}\mrightarrow{}  \mBbbN{}N.  (Inj(\mBbbN{}s  i;\mBbbN{}N;f)  \mwedge{}  (\mforall{}a,b:\mBbbN{}s  i.    (f  a  <  f  b  {}\mRightarrow{}  ((g  (f  a)  (f  b))  =  i))))
3.  s  :  \mBbbN{}c  {}\mrightarrow{}  \mBbbN{}
4.  \mneg{}(c  =  0)
5.  c  =  1
6.  \mneg{}0  <  s  0
\mvdash{}  \mexists{}N:\mBbbN{}\msupplus{}
      \mforall{}g:\mBbbN{}N  {}\mrightarrow{}  \mBbbN{}N  {}\mrightarrow{}  \mBbbN{}1
          \mexists{}i:\mBbbN{}1.  \mexists{}f:\mBbbN{}s  i  {}\mrightarrow{}  \mBbbN{}N.  (Inj(\mBbbN{}s  i;\mBbbN{}N;f)  \mwedge{}  (\mforall{}a,b:\mBbbN{}s  i.    (f  a  <  f  b  {}\mRightarrow{}  ((g  (f  a)  (f  b))  =  i))))
By
Latex:
TACTIC:((D  0  With  \mkleeneopen{}1\mkleeneclose{}    THEN  Auto)  THEN  (D  0  With  \mkleeneopen{}0\mkleeneclose{}    THENA  Auto))
Home
Index